Rapid diagnosis of tuberculosis and multidrug resistance by the microscopic-observation drug-susceptibility assay. - Shah, N Sarita; Moodley, Prashini; Babaria, Palav; Moodley, Salona; Ramtahal, Melissa; Richardson, Jessica; Heysell, Scott; Li, Xuan; Moll, Anthony; Friedland, Gerald; Sturm, A Willem; Gandhi, Neel R (American journal of respiratory and critical care medicine, 2011)
Mortality is exceedingly high and rapid among patients infected with HIV and tuberculosis (TB), in part because of limited access to appropriate TB diagnostics. The microscopic observation drug-susceptibility (MODS) assay is a simple, rapid, low-cost test for TB and multidrug-resistant (MDR) TB, but data in individuals infected with HIV and in Africa are limited.
Keywords: Adult; Antitubercular Agents; Female; HIV Infections; Humans; Male; Microbial Sensitivity Tests; Middle Aged; Mycobacterium tuberculosis; Prospective Studies; Reproducibility of Results; Sensitivity and Specificity; South Africa; Sputum; Tuberculosis; Tuberculosis, Multidrug-Resistant